A processing system for walnut shell - Li Changming (2016)
The utility model discloses a processing system for walnut shell, including cleaning machine, conveying frame, drying -machine and breaker, the cleaning machine is equipped with drain pipe and feed opening, and the breaker is equipped with feed inlet and discharge gate, be equipped with conveyer in the conveying frame, conveyer's feed end is located the below of feed opening, and conveyer's discharge end is located the top of the feed inlet of breaker, the drying -machine is installed and form the region of drying on being lain in the conveying frame between feed end and the discharge end, and conveyer passes the drying -machine along direction?of?delivery. The utility model discloses simple structure, reasonable in design can changing waste into valuables, has practiced thrift the resource, and environmental protection moreover forms the new material after can processing dumped walnut shell, has effectively solved the walnut shell and has been hard to the problem handled. 本实用新型公开了种用于核桃壳的处理系统，包括清洗机、传送机架、烘干机和破